From tiger to bailout: the Irish crisis - Clancy, Paula; McDonnell, Tom (Brussels, 2011)
"The first ETUI Policy Brief European Economic and Employment Policy of 2011 is devoted to analysing the reasons behind Ireland's fall from grace, describing the treatment currently being administered, and setting out progressive policy alternatives for the future. The authors, Paula Clancy and Tom McDonnell, show how Ireland’s deep financial and economic crisis results from failings in its growth model, policy mistakes and systemic failures within European Monetary Union. They analyse the reasons why the bail-out agreement with the IMF and the European authorities and the associated austerity package will not resolve the problems faced by the country and must be renegotiated."